Efficacy and safety of zuberitamab in the treatment of primary membranous nephropathy: an observational study - Zong, Li; Wang, Sha; Zhao, Ke; Lv, Fang-yi; Qian, Shan-kui; Yang, Xiang-dong (Frontiers in Immunology, 2026)
Research BackgroundB lymphocyte-mediated adaptive immunity is pivotal in the pathogenesis of membranous nephropathy (MN). This study evaluated the efficacy and safety of zuberitamab, a novel anti-CD20 monoclonal antibody, in primary membranous nephropathy (PMN).Research MethodsWe retrospectively analyzed 25 patients with PMN treated with zuberitamab (zuberitamab group). Using 1:1 propensity score matching, we selected a comparable control cohort of 25 PMN patients who received rituximab during the same period (RTX group). The primary endpoint was the 12-month overall remission rate (CR + PR).Research ResultsAll 25 patients (100.0%) in the zuberitamab group achieved clinical remission (CR 80.0%) at 12-month, with 11 patients achieving complete immunological remission. Compared to the RTX group, the complete remission (CR) rate was significantly higher (80.0% vs 32.0%, P<0.01). Kaplan-Meier analysis demonstrated a higher complete remission rate (log-rank P<0.001; HR = 4.187, 95% CI [2.285-7.672]). Zuberitamab induced progressive urine protein-to-creatinine ratio (uPCR) reduction (all P<0.001) and sustained albumin improvement (3-month: P<0.05; 6/9/12-month: P<0.001). Peripheral blood CD19+ B-cell counts decreased to < 5 cells/μl at 6-month among the 22 patients with complete follow-up data, and remained consistently low throughout follow-up. No severe adverse events were observed in either group.ConclusionZuberitamab may be a promising treatment option for PMN, demonstrating a high complete remission rate and sustained proteinuria reduction in this study. Large-scale prospective studies are warranted to confirm these findings.